Transition of Metabolic Phenotypes and Risk of Atrial Fibrillation According to BMI: Kailuan Study - Zhao, Maoxiang; Du, Wenjuan; Zhao, Qianqian; Chen, Yating; Li, Bin; Xie, Zhonghui; Fu, Zihao; Zhang, Nan; Cheng, Xiaowei; Li, Xiaoqian; Yao, Siyu; Wang, Miao; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objective: Atrial fibrillation (AF) is associated with both obesity and its metabolic consequences. However, there is a paucity of information on whether the dynamic change of metabolic health and obesity phenotypes affect the risk of AF. We aimed to prospectively examine the association between metabolic health and its change over time and AF risk across BMI categories. Methods: A total of 58483 participants without history of cancer, and cardiovascular disease from Kailuan study were included in the present study. Transition of metabolic phenotypes were evaluated between1st survey (2006-2007) and the 2nd survey (2008-2009). The hazard ratios (HRs) and 95% confidence intervals (CIs) for AF were assessed by Cox proportional hazards regression Results: During a median follow-up of 3 years, we documented 580 cases of AF. Compared with metabolically healthy individuals with normal weight, the multivariable-adjusted hazard ratios for metabolically healthy and unhealthy overweight/obese were 1.27 (95% CI: 1.01, 1.59) and 1.37 (95% CI: 1.09, 1.72), respectively. However, when transition was taken into account, overweight/obese people who maintained metabolically healthy status were not associated with increased long-term risk (HR, 1.11;95% CI:0.70, 1.78), whereas participants who converted from metabolically healthy overweight/obese status to an unhealthy phenotype had higher AF risk than those who maintained metabolically healthy normal weight (HR 1.59, 95% CI: 1.11, 2.26). When BMI and metabolically healthy status were updated over the course of the study, significant short-term elevations in AF risk were associated with individuals with stable MU-OW/OB status. Conclusion: In this community-based cohort study, metabolically healthy overweight/obese individuals have increased risks of AF. Obesity remains a risk factor for AF independent of major metabolic factors. Our data further suggested that metabolic phenotype was a dynamic condition, and maintenance of metabolic health and normal weight might alleviate the risk of AF.